Active Learning Strategies for Engaging Students in Higher Education - Gosavi, Chhaya S.; Arora, Sandhya (Journal of Engineering Education Transformations, 2022)
Rapid development in teaching-learning and its methodologies, technology has opened entirely new avenues for educational research. In active learning, students are exposed to course material through problem solving, case studies, discussion, think pair share, flipped classroom, role play, quizzes, gaming and other pedagogical methods. This proposed work experiments with multiple active learning approaches to engage and motivate reluctant learners. Learners are exposed to the purpose and design of active learning strategies such as quiz, game, case study and role play. Feedbacks and analysis of these implemented active learning strategies are excellent. Statistical analysis of active learning techniques indicates that there is improvement in student’s academic performance, skills development and student’s satisfaction. There exists a great deal of inter-relatedness across the strategies as one strategy invokes another by default. This work will help identify more targeted ways to assist teachers/learners in their efforts.